Implementing creative activities for Class II students to foster independence.: Menguatkan Karakter Mandiri Siswa Sekolah Dasar Kelas II selama PPKM: Strategi, Indikator, dan Implikasinya - Gita Nur Laili; Muhlasin Amrullah (Academia Open, 2023)
This qualitative study aimed to explore the strengthening of independent characters among Class II elementary school students during the Period of Restrictions on Community Activities (PPKM). The research utilized observation, interviews, and documentation as data collection techniques, with the principal, Class II teachers, and guardians of Class II students as subjects. The analysis revealed that four indicators for strengthening independent character were identified within the learning process, despite some suboptimal outcomes influenced by various factors, including students themselves, teachers, and parents. The main strategy employed to enhance independent character was the involvement of parents in providing reinforcement, along with the teachers serving as positive role models. The most frequently implemented indicator for independent character strengthening was completing tasks without disturbing others, employing critical thinking and problem-solving approaches. Moreover, teachers fostered independent characters throughout all learning activities and actively cooperated with parents. These findings highlight the importance of cultivating independent character in elementary schools, emphasizing the significance of self-reliance, critical thinking, and cooperative learning. The implications of this study can inform educators, parents, and policymakers in designing effective interventions to foster independent characters among elementary school students during challenging periods such as PPKM. Highlights: Importance of parental involvement: The study emphasizes the significance of parents' participation in strengthening the independent characters of Class II students during the PPKM period. Role modeling by teachers: Teachers play a crucial role in setting a positive example and modeling independent character traits for students in the learning process. Fostering critical thinking and problem-solving: The implementation of critical thinking and problem-solving models in classrooms contributes to the development of independent characters among Class II students. Keywords: Strengthening independent characters, Class II students, PPKM, Qualitative research, Learning process